A New Sprıng Desıgn On The Treatment Of Dental Telescopıc Bıtes - Enis Güray; Cenk Doruk (Turkish Journal of Orthodontics, 1992)

(untitled)
In this study, telescopic bites (Buccal cross bites) and the choises of treatment has been investigated and a new designed spring which is used on dental telescopic bites has been presented. With the relation of this study, two cases has been introduced.